Efficiency of sperm-mediated gene transfer in the ovine by laparoscopic insemination, in vitro fertilization and ICSI - Pereyra Bonnet, Federico (2011)
Fil: Pereyra Bonnet, Federico. Universidad de Buenos Aires. Facultad de Agronomía. Laboratorio de Biotecnología Animal. Buenos Aires, Argentina.